The Ionomics of Lettuce Infected by Xanthomonas campestris pv. vitians - Nicolas, Olbert; Charles, Marie Thérèse; Jenni, Sylvie; Toussaint, Vicky; Parent, Serge-Étienne; Beaulieu, Carole (Frontiers in Plant Science, 2019)
Bacterial leaf spot (BLS) caused by Xanthomonas campestris pv. vitians (Xcv) places a major constraint on lettuce production worldwide. The most sustainable strategy known to date for controlling BLS is the use of resistant cultivars. The nutrient elemental signature (ionome) of ten lettuce cultivars with three levels of resistance was analyzed by inductively coupled plasma optical emission spectroscopy (ICP-OES) to determine which nutrient balances are linked to resistance to BLS, and to assess the effect of Xcv infection on the ionome. The elemental concentrations were preprocessed with isometric log-ratios to define nutrient balances. Using this approach, 4 out of 11 univariate nutrient balances were found to significantly influence the resistance of lettuce cultivars to BLS (P < 0.05). These significant balances were the overall nutritional status balancing all measured nutrients with their complementary in the dry mass, as well as balances [Mn | Zn, Cu], [Zn | Cu] and [S, N | P]. Moreover, the infection of lettuce cultivars mostly affected the lettuce ionome on the [N,S | P] balance, where infection tended to lean its balance toward the N, S part relatively to P. This study shows that nutrient uptake in lettuce can be affected by BLS infection, and that nutrient status influences resistance to BLS infection.